Exchange control system - An overview / Norashikin Ismail - Ismail, Norashikin (Universiti Teknologi MARA Cawangan Pahang, 2000)
The scope of the exchange control system is considerably wide and its development is never static. As far as possible, the paper attempts to outline the general aspects of control, including its definition and classification, its objectives and historical development. The practical aspects such as the control environment, the legal, administrative and implementation, as well as the common problems, effectiveness and the need to revise and reform the control system will also be included.